Price transmission mechanism for natural gas in Thailand - Natnicha Nimmonrat (2018)
© 2018, Springer International Publishing AG. This study aimed to analyze natural gas price transmission in Thailand using the MS-VAR model. We focused on the data set related to Thai natural gas prices in two main groups. The first group is the price of natural gas procurement source, including price of gulf gas, natural gas price of Myanmar and price of liquefied natural gas. Second group is the prices of natural gas used for electric power generation, separation plants, and production of compressed natural gas, which are considered as natural gas consumption. The data is collected from M1/2011 to M12/2016. By using the Bayesian approach, we estimated the model with two regimes; namely high price regime and low price regime. We found that the shocks e.g., energy crisis, the shortage of natural gas sources from the gulf gas of Thailand or Myanmar stopping selling natural gas to Thailand may have a direct substantial effect on the natural gas market. Therefore, the shocks of each natural gas sources price will have implications on other natural gas sources price and thereby leading are higher consumption costs.